Islamic Cognitive Behavior dalam Menangani Minat Belajar Rendah (Jurnal Bimbingan dan Konseling Islam, 2021)
Islamic behavioral cognitive counseling is a counseling process to create a positive, rational, logical, and adaptive mindset through the values ??of the Qur'an and hadith. Researchers used Islamic Cognitive Behavior to be applied to female students at the Assalafi Al-Fithrah Islamic Boarding School in Surabaya who experienced impaired interest in learning because they were motivated by their own negative thoughts. The counseling process includes problem identification, diagnosis, prognosis, treatment, as well as evaluation and follow-up. The treatment refers to the 12 steps in Islamic cognitive behavioral counseling based on Ibrahim Elfiky's positive thinking therapy. Researchers developed this treatment by integrating techniques in the cognitive behavioral approach and positive thinking therapy belonging to Ibrahim Elfiky which includes the values ??contained in the Qur'an or hadith. Changes in behavior in the form of being willing to enter class according to schedule, rarely sleeping when the teacher delivers lessons, and returning to focus on the subjects delivered by the teacher.